Fish Extract Fractionation by Solid Phase Extraction: Investigating Co-Occurring Ciguatoxins by LC-MS/MS and N2a-Bioassay - Astrid Spielmeyer; Vincent Blaschke; Christopher R. Loeffler (Separations, 2024)
Ciguatoxins (CTXs) are neurotoxic marine biotoxins capable of contaminating marine organisms. Approximately 30 CTX analogues have been described; however, only a few have been documented in ciguatera poisoning (CP) outbreaks. Detecting CTXs from complex matrices at CP-relevant concentrations (<1 µg per kg seafood tissue) is analytically challenging. Analytical standards for CTXs are rare. Even after multi-step sample preparation (including liquid–liquid partition, defatting, and solid-phase extraction (SPE)), extracts can contain undesirable co-eluting matrix components. These limitations can exacerbate discrepancies between results obtained by LC-MS/MS and the N2a-bioassay, which are two common CTX detection methods. Herein, a rapid and simple fractionation method, based on normal phase SPE (silica), is demonstrated. Target CTXs were eluted using solvent mixtures of ascending polarity, passed through the column, and separated into eight fractions. To challenge the method, extracts with eleven naturally incurred CTX analogues among different structural CTX groups (e.g., CTX3C, CTX4A, and C-CTX group) were used. The most complex tissue matrix tested (viscera) was improved the most for extract purity and CTX detection, enhancing the correlation between LC-MS/MS and N2a-bioassay results. This workflow represents an advancement for characterizing CTXs in seafood products and CP outbreaks, irrespective of the responsible CTX analogue and where standards are lacking.